1927 Haw. Sess. Laws 209-217, AN ACT Regulating the Sale, Transfer and Possession of Certain Firearms and Ammunitions, and Amending Sections 2136, 2137, 2138, 2139, 2140, 2141, 2142, 2143, 2146 and 2147 of the Revised Laws of Hawaii 1925 (the "Small Arms Act"), § 8 - (:unkn) unknown (General Publisher, 1927)
Prohibited the sale, barter, hiring, lending, or giving a pistol or revolver to any person under the age of eighteen.
--
Keywords: TRANSFER - MINORS